The Swedish Red List 2025 – including ecological variables - Swedish Species Information Centre, Swedish University of Agricultural Sciences (Swedish University of Agricultural Sciences, 2026)
The Swedish Red List is compiled by the Swedish Species Information Centre (SLU Artdatabanken) at the Swedish University of Agricultural Sciences as part of the environmental monitoring and assessment programme Biodiversity. It includes assessments of the extinction risk of species in Sweden. The Swedish Red List 2025 was published on 24 March 2026 and is the sixth Swedish Red List to use the International Union for Conservation of Nature (IUCN) Red List categories and criteria.

During the Red List assessment process, the basis for the assessments varies greatly between different species. Some species groups, such as birds and many mammals and fish, are covered by thorough environmental monitoring with long time series of data. However, for most other species groups, the level of knowledge is considerably more limited, which is taken into account in the Red List assessment methodology. To better understand the assessments, it may be helpful to read Manual och riktlinjer för rödlistning i Sverige 2025 (https://res.slu.se/id/publ/145574).

This dataset includes all species that have been categorized as red-listed: Regionally Extinct (RE), Critically Endangered (CR), Endangered (EN), Vulnerable (VU), Near Threatened (NT) and Data Deficient (DD). The dataset consists of three different data files that are available as separate CSV files or as a single Excel file with multiple sheets.

The data file/sheet ”Rodlistade_arter_2025” contains all red-listed species and their assigned categories, the criteria leading to the red-list categories and supporting documentation. It also includes information on factors that may negatively affect species’ survival in Sweden, as well as information about the species' regional occurrence, and their association with landscape types, biotopes and substrates. The data file/sheet consists of 5217 rows and 128 columns.

The data file/sheet ”Paverkan_taxonrelationer” contains information for the two impact factors where the effects on red-listed species are specified in relation to other taxa. The compiled values for red-listed species that have one or more values associated with different taxon relationships for these factors are presented in the data file/sheet “Rodlistade_arter_2025”. The data file/sheet consists of 556 rows and 13 columns.

The data file/sheet ”Substrat_taxonrelationer” contains information for the nine substrate factors where the values for red-listed species are specified in relation to other taxa. The compiled values for red-listed species that have one or more values associated with different taxon relationships for these factors are presented in the data file/sheet “Rodlistade_arter_2025”. The data file/sheet consists of 7035 rows and 30 columns.

This dataset contains only species and does not include other taxon categories. For an overview of all red-listed taxa, including subspecies, apomictic species and other taxon categories, refer to the dataset “Red List work 2025: All red-listed taxa as well as all taxa in the categories Least Concerned (LC), Not Evaluated (NE) and Not Applicable (NA)” at the Swedish National Data Service (https://doi.org/10.5878/ffrv-6x57). An overview of all red-listed taxa and their categories is also available in the dataset ”The Swedish Red List 2025” at the Global Biodiversity Information Facility (GBIF, https://doi.org/10.15468/zbbyqv).

Sveriges rödlista tas fram av SLU Artdatabanken vid Sveriges lantbruksuniversitet inom miljöanalysprogrammet Biologisk mångfald, och är en sammanställning av arters utdöenderisk inom landets gränser. Rödlistade arter i Sverige 2025 publicerades den 24 mars 2026, och är den sjätte rödlistan för Sverige där internationella naturvårdsunionens (International Union for Conservation of Nature, IUCN) kategorier och kriterier för rödlistning används.

Under arbetet med rödlistning ser underlagen för bedömningarna mycket olika ut för olika arter. Vissa artgrupper, som fåglar samt många däggdjur och fiskar, omfattas av en noggrann miljöövervakning med långa tidsserier av data. Men för de flesta andra artgrupper är kunskapen betydligt mer begränsad, något som metodiken för rödlistning tar hänsyn till. För att bättre förstå bedömningarna kan det vara till hjälp att ta del av Manual och riktlinjer för rödlistning i Sverige 2025 (https://res.slu.se/id/publ/145574).

Detta dataset omfattar arter som har fått en kategori som rödlistad: Nationellt utdöd (RE), Akut hotad (CR), Starkt hotad (EN), Sårbar (VU), Nära hotad (NT) och Kunskapsbrist (DD). Datasetet består av tre olika datafiler. Dessa kan antingen laddas ner som tre separata csv-filer eller som en Excelfil bestående av flera flikar.

Datafilen/fliken ”Rodlistade_arter_2025” innehåller samtliga rödlistade arter och deras kategorier, utfallsgivande kriterier och kriteriedokumentation. Utöver detta återges även faktorer som kan ha negativ påverkan på arternas överlevnad i Sverige, samt information om arternas länsförekomst, och deras koppling till landskapstyper, biotoper och substrat. Datafilen/fliken omfattar 5217 rader och 128 kolumner.

Datafliken ”Paverkan_taxonrelationer” innehåller information för de två påverkansfaktorer där effekterna på rödlistade arter är specificerade i relation till andra taxa. De sammanställda värdena för rödlistade arter som har ett eller flera värden kopplade till olika taxonrelationer för dessa faktorer återges i datafilen/fliken ”Rodlistade_arter_2025”. Datafilen/fliken omfattar 556 rader och 13 kolumner.

Datafilen/fliken ”Substrat_taxonrelationer” innehåller information för de nio substratfaktorer där substratvärdena för rödlistade arter är specificerade i relation till andra taxa. De sammanställda värdena för rödlistade arter som har ett eller flera värden kopplade till olika taxonrelationer för dessa faktorer återges i datafilen/fliken ”Rodlistade_arter_2025”. Datafilen/fliken omfattar 7035 rader och 30 kolumner.

Detta dataset omfattar enbart arter och inkluderar inga andra taxonkategorier. För en översikt över alla rödlistade taxa, inklusive underarter, apomiktiska arter och andra taxonkategorier, hänvisas till datasetet ”Rödlistearbete 2025: Alla rödlistade taxa samt alla taxa i kategorierna Livskraftig (LC), Ej bedömd (NE) och Ej tillämplig (NA)” hos Svensk Nationell Datatjänst (SND, https://doi.org/10.5878/ffrv-6x57). En översikt över alla rödlistade taxa och deras kategorier finns även i datasetet ”The Swedish Red List 2025” hos Global Biodiversity Information Facility (GBIF, https://doi.org/10.15468/zbbyqv).
Rödlistade arter i Sverige 2025 – med ekologiska variabler
Rödlista 2025
Keywords: ENDANGERED SPECIES; red list; endangered animal species; utrotningshotade djurarter; endangered plant species; utrotningshotade växtsorter; endangered species (IUCN); utrotningshotade arter (IUCN); landscape conservation; naturvård; conservation of species; biodiversity conservation; biodiversity; biologisk mångfald; conservation; skydd; biodiversity loss; endangered species; IUCN red list species; threatened species; near threatened species; nära hotade arter; Bacteria; eubakterier; Animalia; flercelliga djur; Fungi; svampar; Chromista; kromister; Plantae; egentliga växter; red list assessment; rödlistebedömning; Botany; Botanik; Zoology; Zoologi; Ecology; Ekologi; Other Biological Topics; Annan biologi